Clinical and immunological features in children with multisystem inflammatory syndrome associated with SARS-CoV-2: Clinical and immunological features in children with MIS-C - Jaxybayeva, Indira; Boranbayeva, Riza; Bulegenova, Munira; Urazalieva, Nataliya (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: MIS-C is characterized by intense immune activation and increased production of cytokines. The aim of our study was to analyse the changes of cellular and humoral immune responses in children with MIS-C, depending on the severity of the disease. Methods: To conduct the study, the results of clinical, hematological and immunological parameters in children with severe and extremely severe MIS-C were compared. A total of 50 patients participated in the study, which were divided into 3 groups, of which: 20 children with extremely severe MIS-C treated in the ICU (MIS-C ICU "+"); 15 children with severe MIS-C, but without the need for hospitalization in the ICU (MIS-C ICU "-"); 15 children who had COVID-19 and absence MIS-C (MIS-C "-") made up the control group. Results: In patients with MIS-C hospitalized in the ICU, heart and liver damage, hematological changes, and the development of severe complications such as edematous syndrome, polyserositis, DIC, and cardiogenic shock were statistically more common. Both groups of children with MIS-C had CD3+ T-cell lymphopenia and a decrease in CD95 expression. In the group of children with MIS-C hospitalized in the ICU, a significant increase in the relative number of B-lymphocytes, CD3-HLA-DR+ and CD25 and decrease of NK-cells was observed. Conclusions: The risk of hospitalization in the ICU in children with MIS-C is associated with more profound immune dysregulation, as evidenced by our data. (www.actabiomedica.it)